The Effect of Service Quality and Marketing Mix On Customer Satisfaction and Trust in Building Loyalty: B2B Customers of PT. Farmsco Feed Indonesia - Iskandar, Rhegy Pratidina; Hartoyo; Yulianti, Lilik Noor (Jurnal Manajemen & Agribisnis, 2023)
The livestock industry is an economic sector with high potential for generating quality economic growth. This study aims to analyze the effects of service quality and marketing mix on satisfaction, trust, and customer loyalty of PT. Farmsco Feed Indonesia (PT.FFI), as well as to formulate managerial implications that companies can apply to increase customer loyalty. The research design used in this study is quantitative, utilizing a survey approach. The sample consists of B2B (Business to Business) customers of PT. FFI who have been using poultry feed for the past two years. A total of 157 individuals were selected through voluntary sampling. Data were collected through an online survey using a Google Form questionnaire. The independent variables in the study are service quality and marketing mix, while the dependent variables are trust, satisfaction, and loyalty. Data processing and analysis techniques involved descriptive analysis and Structural Equation Modelling. The results indicate that: 1) service quality variables do not have a significant effect on satisfaction and loyalty, 2) the marketing mix has a significant effect on satisfaction and trust, 3) trust has a significant effect on customer loyalty, and 4) managerial implications for increasing customer loyalty include enhancing customer trust to foster long-term relationships. Keywords: customer loyalty, marketing mix, satisfaction customer, service quality, B2B customers